Reconstructive Trends After Tissue-Expander Loss in Breast Reconstruction. (May 2022) - Ghosh, Kanad; Marquez, Jocellie; Niu, Ellen; Rogoff, Hunter; Monroig, Kaitlin; Marmor, William; Kianian, Sara; Bui, Duc T.; Huston, Tara L.
Abstract : Purpose: Tissue-expander breast reconstruction (TEBR) is a common method of reconstruction after mastectomy but may result in complications that may necessitate removal. Although complications in TEBR have been well studied, there is a paucity of data regarding outcomes after tissue-expander loss. In this study, we examine the eventual reconstructive pathways and associated factors of patients who required tissue-expander removal after infection. Methods: This retrospective study examines patients undergoing breast reconstruction at a single institution. Patients included underwent mastectomy, immediate TEBR, and subsequent tissue-expander loss. Patients who underwent autologous reconstruction after mastectomy or had successful TEBR were excluded. Patients were followed for an average of 7 years, with a minimum of 2 years and a maximum of 13 years. Results: A total of 674 TEBR patients were initially screened, of which 60 patients (8.9%) required tissue-expander removal because of infection or skin necrosis. Thirty-one of these patients (group 1) did not complete reconstruction after initial tissue-expander loss, whereas the remaining 29 patients (group 2) underwent either TEBR or autologous reconstruction after tissue-expander loss. Group 1 had a significantly higher mean body mass index than group 2 (32.61 ± 8.88 vs 28.69 ± 5.84; P = 0.049) and also lived further away from our institution than group 2 ( P = 0.052), which trended toward significance. There were otherwise no significant differences in demographics between the 2 groups. Among the 29 patients in group 2, 18 patients underwent a second TEBR (group 2a), and 11 patients underwent autologous reconstruction (group 2b). Patients in group 2b had a significantly greater mean number of complication related admissions (1.11 ± 0.323 vs 1.55 ± 0.688; P = 0.029) and also had higher occurrence of postmastectomy radiation therapy (16.7% vs 45.5%; P = 0.092), although this was not significant. There were otherwise no differences between the 2 groups. Conclusion: Our data demonstrate the trends in breast reconstruction decision making after initial tissue-expander loss. This study elucidates the factors associated with patients who undergo different reconstructive options. Further work is needed to delineate the specific reasons between the decision to pursue different reconstructive pathways among a larger cohort of patients.